Effect of iron injections on aerobic-exercise performance of iron-depleted female athletes - Peeling, P.; Blee, T.; Goodman, C.; Dawson, B.; Claydon, G.; Beilby, J.; Prins, A. (International Journal of Sport Nutrition and Exercise Metabolism, 2007)
This investigation examined the effect of intramuscular iron injections on aerobic-exercise performance in iron-deficient women. Sixteen athletes performed a 10-min steady-state submaximal economy test, a VO2max test, and a timed test to exhaustion at VO2max workload. Subjects were randomly assigned to an iron-supplemented group (IG) receiving intramuscular iron injections or to a placebo group (PG). Twenty days after the first injection, exercise and blood testing were repeated. A final blood test occurred on Day 28. Postsupplementation, no differences were found between the groups' submaximal or maximal VO2, heart rate, or blood lactate (P > 0.05). Time to exhaustion was increased in the IG (P < 0.05) but was not greater than that of the PG (P > 0.05). The IG's serum ferritin (SF) was significantly increased on Days 20 and 28 (mean ± standard error: 19 ± 3 to 65 ± 11 to 57 ± 12 µg/L; P < 0.01), with a percentage change from baseline significantly greater than in the PG (P < 0.01). It was concluded that intramuscular iron injections can effectively increase SF without enhancing submaximal or maximal aerobic-exercise performance in iron-depleted female athletes.